A size-dependent model for predicting the mechanical behaviors of adhesively bonded layered structures based on strain gradient elasticity. (15th May 2021) - Long, Hao; Ma, Hansong; Wei, Yueguang; Liu, Yanwei
Highlights: A size-dependent model of adhesively bonded layered structures based on strain gradient elasticity is proposed. Size effects of the local interfacial tractions and global adherend displacement are presented. The global adherend displacement is insensitive to the adhesive modulus for micro-scale adhesive layers. Influences of the geometry and material parameters on the interfacial tractions and adherend displacement are discussed. Abstract: As adhesively bonded layered devices scale down, micro-scale adhesive layers become common and play a key role in the overall performance of micro devices. Herein, we use the strain gradient elasticity to characterize the micro-scale adhesive layers and propose an analytical size-dependent model to predict the mechanical behaviors of adhesively bonded layered structures. The results indicate that the local interfacial tractions and the global adherend displacement both show strong size effects, especially for soft adhesives with low modulus. When the ratio of the adhesive layer thickness to its material characteristic length scale (on the order of microns), representing the scale of the layered structures, decreases to unity, the interfacial tractions increase substantially and the adherend displacement decreases significantly. Meanwhile, the adherend displacement is insensitive to the adhesive modulus. The present study reveals the stiffening behaviors of layered structures, which are attributed to the large strain gradients in the constrained micro-scale adhesive layers. The results can help us predict the deformation of adhesively bonded layered structures, and achieve high performance of micro devices by adhesive bonding. Graphical abstract: Image, graphical abstract